Culture Incorporated Museums, Artists, and Corporate Sponsorships - Mark W. Rectanus (University of Minnesota Press, 2002)
As the advertisement suggests, sponsorships are now embedded in many facets of contemporary culture: cultural programs (from historic restorations to rock concerts), social sponsorships (of education, health, and environmental programs), or sports sponsorships. The borders between the social, cultural, and political, which sponsoring ostensibly maintains, dissolve in the practice of corporate cultural politics. This is underscored by the shift from separate programming for cultural and social sponsorships to new programs that integrate cultural and social projects, both locally, in the communities where corporations maintain their operations, and globally, in their promotion of products and images. Corporate cultural politics attempt to legitimize corporate interests in globalized societiesâ€”in cultural, social, economic, and political spheresâ€”but in doing so they also expose their stake in institutional and communal discourses and values. Not only has the corporation become accepted as a legitimate, institutionalized participant in the cultural marketplace, but corporate cultural politics also define and shape culture. Associating cultural sponsorship exclusively with â€œhigh cultureâ€ or patronage masks the corporationâ€™s participation in constructing social relations and identities in a multidimensional culture of everyday life, a culture that cannot be adequately characterized as high or low. Culture Incorporated argues that an analysis of sponsorship, as a function of corporate cultural politics, is now more crucial than ever, precisely because sponsoring has become so ubiquitous. Sponsorships deflect attention away from the corporationâ€™s own functions as a cultural producer, promoter, or mediator by projecting the image of an institutional entity standing outside the cultural marketplace.